2017
DOI: 10.1016/j.trf.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The exact determination of subjective risk and comfort thresholds in car following

Abstract: In this study the location of vehicle to vehicle distance thresholds for self-reported subjective risk and comfort was researched. Participants were presented with ascending and descending time headway sequences in a driving simulator. This so called method of limits of ascending and descending stimuli (Gouy, Diels, Reed, Stevens, & Burnett, 2012) was refined to efficiently determine individual thresholds for stable time headways with a granularity of 0.1 seconds. Time headway thresholds were researched for 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
3
18
2
Order By: Relevance
“…Time gap shows almost no correlation with the host vehicle speed. This is analogous to the results in [38][39][40], that is, distance headway increases as the host vehicle speed increases and time headway is nearly constant in different speed ranges. However, time headway is described to decrease as the host vehicle speed increases in [22], [41,42].…”
Section: Comparison Of Ttc and Time Gap In Various Relative Speed supporting
confidence: 86%
“…Time gap shows almost no correlation with the host vehicle speed. This is analogous to the results in [38][39][40], that is, distance headway increases as the host vehicle speed increases and time headway is nearly constant in different speed ranges. However, time headway is described to decrease as the host vehicle speed increases in [22], [41,42].…”
Section: Comparison Of Ttc and Time Gap In Various Relative Speed supporting
confidence: 86%
“…A large number of studies have found that drivers follow other vehicles with a constant time headway at different speeds, and prefer constant time headway following to non-constant following when presented with a number of time headways at different speeds (Ayres, Li, Schleuning, & Young, 2001;Siebert et al, 2014Siebert et al, , 2017Taieb-Maimon & Shinar, 2001;Van Winsum & Heino, 1996). Siebert et al (2014Siebert et al ( , 2017 researched car following preferences for the use of adaptive cruise control and found stable individual time headway preferences. Most preferred headways in self-and assisted-driving are found in the range of one to two seconds in simulated as well as in real-life driving, although preferred time headways of individual drivers differ.…”
Section: Constant Time Headway Followingmentioning
confidence: 99%
“…Most preferred headways in self-and assisted-driving are found in the range of one to two seconds in simulated as well as in real-life driving, although preferred time headways of individual drivers differ. In all earlier studies on the relation between the subjective experience of drivers and time headway, drivers either had complete control over the vehicle (Ayres et al, 2001;Taieb-Maimon & Shinar, 2001;Van Winsum & Heino, 1996), or were actively controlling the steering wheel in studies where an adaptive cruise control system was implemented (Siebert et al, 2014(Siebert et al, , 2017. It is therefore unclear how the complete absence of active control over the vehicle in highly automated driving influences the subjective experience of time headways.…”
Section: Constant Time Headway Followingmentioning
confidence: 99%
See 2 more Smart Citations